TEWI 2021 (Technology, Education, Knowledge, Innovation) - Wojciechowski, Adam (Ed.); Napieralski, Piotr (Ed.); Lipiński, Piotr (Ed.) (Lodz University of Technology Press, 2021)
The monograph TEWI 2021 is a direct response to the demand of the industry, which looks for research projects partners. On the one hand, the material submitted for this monograph will give opportunity for the academic community to present their competencies in the thematic areas of research they conduct. On the other hand, the industry will stimulate the research development of academic staff by outlining current and future areas in the field of modern technologies. The aim of this monograph is to popularize research areas in: 1. technology (information technologies), 2. education (new methods and IT solutions implemented in education), 3. knowledge (practical applications of physics and mathematics in technical sciences), 4. innovation (transfer of new ideas between science and business). [...]
Cover: Andrzejczak, Jarosław
Keywords: information technologies; education; IT solutions in education; knowledge; practical applications of physics; practical applications of mathematics; technical sciences; innovation; good practices; modern teaching methods; Problem Based Learning (PBL)